Analysis of Flexible Forms of Employment in Poland on the Example of Interim Employment - Rękas, Magdalena (Analiza wykorzystania elastycznych form zatrudnienia w Polsce na przykładzie pracy czasowej, 2010)
Modern economies are more and more often based on flexible employment forms which accurately stipulate an employment timeframe. The forms of timeframe employment enable the economies to adjust the level of employment to market conditions and to the level of completed orders. The interim employment is also a chance for employees to escape unemployment. This paper's objective is to characterize forms of employment covered by the definition of the "interim employment" as well as to diagnose the number of contracts for interim employment in Poland between 1997 and 2008. In the conclusion there is an attempt to show desirable trends of changes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 161-172
Keywords: employment; interim employment; flexible forms of employment